Technological interventions in stuttering: A systematic review. - Chaudhary, Chanchal; John, Sunila; Kumaran D, Senthil; Guddattu, Vasudeva; Krishnan, Gopee (Technology & Disability, 2022)
BACKGROUND: Technology in recent times has shown exciting advancements. These advancements have been implemented in healthcare settings to improve therapeutic outcomes. Within the domain of communication disorders, stuttering has witnessed the implementation of a wide variety of technological interventions. This paper provides a comprehensive review of the current status of technology-based stuttering intervention programs, their advantages and disadvantages, and a few directions for future research. AIM: This review aimed to systematically identify the technologies used in stuttering intervention and explore the effect of these interventions on dysfluencies in stuttering. METHOD: We followed the conventional systematic review process and searched six electronic databases using relevant keywords. We included intervention studies published since 1990 on individuals diagnosed with developmental stuttering. In addition, all studies that used technological intervention such as device(s), computer programs, and mobile phone applications were included. RESULT: Fifty-nine studies were included after a thorough eligibility check. The major categories of technological rehabilitation include telehealth technology, software programs, biofeedback, virtual reality, video-self modeling, neuromodulation, and altered auditory feedback. In general, the results show a beneficial effect of technological intervention in reducing stuttering. Further, this review identifies reduction of the duration and minimal to no side effects with such intervention technologies in stuttering. Finally, the percentage of stuttered syllables (%SS) emerged as the most common outcome measure in technology-based intervention in stuttering. CONCLUSION: A wide variety of technological applications have been implemented in stuttering intervention. Regardless of type, all the studies that aimed to examine the effect of the technological intervention on stuttering reported positive outcomes. This review highlights technology-based stuttering intervention programs' current status and their impact on stuttering dysfluencies. Further, it highlights several advantages and disadvantages of implementing technology-based interventions, and a few directions for future research.